THE ROLE OF ORGANIC AND ORGANOMINERAL COMPONENTS IN THEFORMATION OF THE PHOSPHATE REGIME IN PLOUGH HORIZONS OF EROSION-DEGRADED AGRO SODDY-PODZOLIC SOILS - Z. S. Artemieva (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
The soil organic matter is one of the factors affecting the phosphate ionic sorption of soils. Of special interest is the study of sorption characteristics of organo-mineral relationship products in soil. The organic-clay (clay fractions) and organic (fine fractions) complexes play the most important role in developing the soil phosphate regime. Under study was the phosphate state in plough horizons of erosion-degraded agro soddy-podzolic soils as based upon the parameters of the phosphate-ionic sorption in different components of the organic matter. The organic and organomineral fractions of plough horizons in soils that were not subjected to water erosion are characterized by a high level of phosphorus mobility and the capacity to provide a constant amount of phosphates available for plants (Pmob is 17.95±2.06 mg/kg of soil), the low sorption capacity to phosphate-ions (Psorp is 96.06±0.53 mg/kg of soil). Agro-ecological peculiar features of eroded soils are the increased sorption of phosphate-ion (Psorp becomes higher by more than 2 times) and the low level of available phosphorus (Pmob is declined almost by 2 times) as compared to those in uneroded soils. The processes of sediment accumulation promote some improving the soil sorption parameters, what is manifested in increasing the amount of mobile phosphorus in the soil solution and in decreasing the phosphorus sorption by the soil solid phase. In this case Pmob is increasing by more than 20% in washed-out soils, whereas Psorp becomes decreased by 1%. A set of parameters for the phosphate-ionic sorption of organomineral components in the studied soils with different elementary soil structures may serve as an informative system for estimating the phosphate regime in erosion-degraded agro soddy-podzolic soils.